Growth hacking, digital marketing and startup metrics - a data driven approach - Lima, Antonio Miguel Furtado Costa Maia de (2016)
The main goal of the work project is to discuss the importance of analytics and data driven decisions in startup companies, since they are frequently presented as neglected components within startups. In order to understand their benefits for startups several tools were used: literature review, questionnaires, interviews and a Startup Company as a case study. This Startup allowed this work project to focus on analytics and metrics, more precisely on those related with marketing area. Therefore, this work was conducted to propose several suggestions that will allow startups to grow in terms of revenues and users without jeopardizing sustainable growth.